Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
Spain has experienced income convergence consistently in the past decade, despite gradual losses in competitiveness. The empirical evidence indicates that overall EU enlargement offers a range of opportunities for Spain, points to potential pressures in specific sectors, and offers challenges, and tackling the challenges requires a flexible economy. The pattern of Spanish exports is dominated by its off-center location in the Southern part of the EU. Geographical location also plays a central role in determining the origin of foreign direct investment (FDI) flows to Spain.